2009
DOI: 10.1001/archgenpsychiatry.2009.24
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Reductions of Cortical Thickness in Schizophrenia and Spectrum Disorders and Evidence of Heritability

Abstract: Context Schizophrenia is a brain disorder with predominantly genetic risk factors, and previous research has identified heritable cortical and subcortical reductions in local brain volume. To our knowledge, cortical thickness, a measure of particular interest in schizophrenia, has not previously been evaluated in terms of its heritability in relationship to risk for schizophrenia. Objective To quantify the distribution and heritability of cortical thickness changes in schizophrenia. Design We analyzed a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
165
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(206 citation statements)
references
References 68 publications
31
165
1
1
Order By: Relevance
“…Studies have shown widespread cortical thickness reductions across the brain in patients with schizophrenia compared with healthy controls with frontal and temporal regions being generally more affected than others areas (Nesvåg et al 2008;Goldman, 2009;Schultz et al 2010). In line with prior work, Ehrlich et al (2012) and Geisler et al (2015) recently reported marked reductions of cortical thickness in patients with schizophrenia, which were also related to executive functioning.…”
Section: Introductionsupporting
confidence: 72%
“…Studies have shown widespread cortical thickness reductions across the brain in patients with schizophrenia compared with healthy controls with frontal and temporal regions being generally more affected than others areas (Nesvåg et al 2008;Goldman, 2009;Schultz et al 2010). In line with prior work, Ehrlich et al (2012) and Geisler et al (2015) recently reported marked reductions of cortical thickness in patients with schizophrenia, which were also related to executive functioning.…”
Section: Introductionsupporting
confidence: 72%
“…Increased average head size, childhood brain volume, or cortical thickness in individuals with: (i) idiopathic autism (50-53), (ii) the autism-associated duplications at 1q21.1 (17) and 16p13.1 (32) and the autism-associated deletions at 16p11.2 (31), and (iii) autism due to loss of function (or haploinsufficiency) of FMR1 (54), NF1 (55), PTEN (56) and RNF135 (57). By contrast, reduced average values for brain size and cortical thickness, due to some combination of reduced growth and accelerated gray matter loss, have been demonstrated with notable consistency across studies of schizophrenia (58)(59)(60)(61)(62), and such reduced head or brain size has also been associated with the schizophrenia-linked CNVs at 1q21.1 and 22q11.21 (17,63,64), and with deletions of 16p13.1 (65).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one of the principal pathological findings in the brains of those affected with schizophrenia involves abnormal cortical thinning (Cannon et al, 2015). Reduced cortical thickness has also been demonstrated in the unaffected siblings of patients with the disorder (Goldman et al, 2009;Goghari, Rehm, Carter, & MacDonald, 2007;Gogtay et al, 2007), suggesting a possible relationship of these cortical changes to the genetic liability for developing the illness. Indeed, schizophrenia's strongest genetic association involves variation in the major histocompatibility complex (MHC) locus, which mediates synapse elimination during postnatal development in mice (Sekar et al, 2016).…”
Section: Structural Abnormalities In Schizophreniamentioning
confidence: 99%